Debt accumulation in the Caribbean : origins, consequences and strategies - Pérez, Esteban (ECLAC Port of SpainTT, 2007)
Analyzes the origins and consequences of debt accumulation in the Caribbean. Focuses on CARICOM economies and examines current strategies for the reduction of debt.